Magnetic Resonance Imaging of Bone Marrow and its Results as a Criterion for Administration of Maintenance Therapy After Auto-HSCT in Multiple Myeloma Patients - MV Solov’ev (Kliničeskaâ onkogematologiâ, 2018)
Aim. To evaluate the efficacy of maintenance therapy in multiple myeloma (MM) patients after autologous hematopoietic stem cell transplantation (auto-HSCT) based on the results of MRI of bone marrow.